Minority topics, ethnic questions and their potential for memory work in schools - Wutti, Daniel (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2021)
Divergent narratives and memories face each other in a certain hierarchy. The dramatic events of the last century are interpreted differently in a democratic and pluralistic society, and different societies hand down disparate hegemonial narratives and counter-narratives. Two recent research projects in the field of memory studies in education have been conducted in the Austrian bilingual region of Kärnten/Koroška. Both projects focused on suspected transformations of memory culture towards more inclusive narratives in educational work. The following article introduces the methodology of these projects, along with new perspectives extracted from the assembled data - with a certain focus on ethnic aspects and the question of minorities in memory culture. Perspectives on how these matters could address and foster contemporary school lessons conclude the article.
Keywords: Avstrija; etničnost; Koroška; kultura spomina; manjšine; spomin drugih; šolstvo; zgodovinsko-politično izobraževanje